ANALISIS PERBEDAAN HARGA, VOLUME PERDAGANGAN, DAN RETURN SAHAM SEBELUM DAN SESUDAH INFORMASI AKUISISI PADA INDUSTRI TELEKOMUNIKASI DAN PROPERTI - Tasa Ushuaia; Bulan Prabawani (Universitas Diponegoro, 2016)
Economic development requires companies to work better and be able to survive from intense competition. In a modern era, telecommunications and property industries are the most developed industry. There are several strategies to maintain the business continuity, one of which is the incorporation of a business entity such as an acquisition. The purpose of this research is to find differentiation among stock price, stock trading volume and stock return before and after acquisition on the telecommunications and property industries. In the telecommunications industry, there is the acquisition of PT. XL Axiata Tbk with Axis Telekom Indonesia, while the acquisition in the property industry is between PT. Agung Podomoro Land Tbk and PT. Graha Cipta Karisma. The observed research period is one year before and after the acquisition information. This study has found that there is a significant difference in the stock price before and after acquisition information of PT. XL Axiata Tbk and PT. Agung Podomoro Land Tbk, but there is no significant difference in trading volume and stock return (indicated by the abnormal return to test the information content of an event) before and after acquisition information of PT. XL Axiata Tbk and PT. Agung Podomoro Land Tbk. Hence, the investor has the assumption that the acquisition is a normal activity which has no significant influence the stock volume and returns.